Randomly-branched polymers by size exclusion chromatography with triple detection : computer simulation study for estimating errors in the distribution of molar mass and branching degree - Vega, Jorge Rubén (2013)
This article theoretically evaluates the biases introduced into the distributions of molar masses (MMD) and the number of long chain branches per molecule (LCBD), when randomly-branched polymers are analyzed by size exclusion chromatography (SEC) with molar mass-sensitive detectors. The MMD of a polymer with tetrafunctional branch units has been calculated with the Stockmayer equation (1943); and an ideal SEC analysis has been simulated that assumes u-solvent, perfect measurements, and perfect fractionation by hydrodynamic volume except for a minor mixing in the detector cells. In ideal SEC, a negligible bias is introduced into the MMD, with the local dispersity exhibiting a maximum of 1.0035 at the high molar masses. This result is consistent with previous theoretical investigations, but differs qualitatively from experimental observationsofpolymerscontainingshort-andlong-chain branches. When including band broadening in the columns while still assuming perfect measurements, the MMDremainsessentiallyunbiased.Incontrast,poorMMD estimates are obtained when the chromatograms are contaminated with additive noise. Only qualitative estimates of the LCBD are possible, due to theoretical limitations combined with propagation of errors in a highly nonlinear calculation procedure.